Exploring ecosystem dynamics through trophic level analysis in the Aegean Sea - KERAMIDAS, IOANNIS; DIMARCHOPOULOU, DONNA; STERGIOU, KONSTANTINOS I.; TSIKLIRAS, ATHANASSIOS C. (Mediterranean Marine Science, 2026)
The present study diagnoses the exploitation status of marine resources in the Aegean Sea using EcoTroph, a trophic modelling framework that builds upon ECOPATH outputs to represent biomass distribution as continuous flows across trophic levels (TLs). The model was applied to an updated ECOPATH snapshot for 2021, derived from a time-dynamic ECOSIM model fitted to biomass and catch data from 2006 to 2021. Results showed that biomass was concentrated at intermediate TLs (2.7-3.3), largely dominated by small pelagic fishes, while high-TL predators and low-TL benthic herbivorous and detritivorous groups exhibited signs of depletion under current fishing pressure. Simulations of increasing effort revealed that intermediate levels still retain the capacity for higher yields, although this potential declines as exploitation intensifies. Exploitation thresholds derived from EcoTroph outputs identified the effort levels corresponding to the maximum sustainable yield and a precautionary limit comparable to the F0.1 reference point. Results indicated that this precautionary threshold (E0.1) has already been exceeded for both low and high TLs, while intermediate TLs remain below it and could sustain limited catch increases before reaching full exploitation. The sensitivity analysis showed that the biomass accessible to fisheries had the strongest influence on catches, whereas top-down control and detritus recycling played smaller roles. Overall, EcoTroph revealed uneven exploitation across the Aegean Sea food web. Mid-trophic species continue to support fisheries, but sustained pressure on predators and benthic groups threatens long-term ecosystem balance.